Morphological Transitions during Au Electrodeposition: From Porous Films to Compact Films and Nanowires. Issue 12 (28th August 2015) - Josell, D.; Levin, I.; Moffat, T. P.
Abstract : Gold electrodeposition was studied in a sulfite electrolyte to which micromolar concentrations of Tl2 SO4 were added. Hysteresis and a regime of negative differential resistance (NDR) evident in electroanalytical measurements are correlated with deposit morphology and interpreted through measurements of thallium underpotential deposition (upd). Deposit morphologies range from specular surfaces to highly faceted dendrite-like grains of moderate aspect ratio and, for potentials within the NDR region, sub-50 nm diameter, high aspect ratio 110 oriented single crystal nanowires. The nanowires exhibit an epitaxial relationship to the substrate that permits one step fabrication of surfaces densely covered with high aspect ratio nanowires having controlled orientations. The NDR and nanowires are a consequence of the non-monotonic relationship between Tl coverage and growth velocity; at low coverage Tl accelerates Au deposition while at higher coverage it inhibits deposition. Immiscibility of the Tl and Au supports on-going surface segregation during area expansion that accompanies nanowire growth leading to greater dilution of the additive coverage and more rapid growth at the nanowire tips, while the sidewalls remain passivated by a saturated Tl coverage.